Attitudes to Entrepreneurship: The Case of Chilean and Spanish University Students [Actitudes Hacia el Emprendimiento: El Caso de Los Estudiantes Universitarios Chilenos y Españoles] - Radrigan-Rubio, M (CIRIEC, 2018)
One of the missions of the university in today s world is to foment and implement processes that help students to find their place in society and become part of its productive structure. One way to achieve this is to motivate them to initiate business ventures. Accordingly, the objective of this research study was to discover the attitudinal variables that influence university students when they decide to start a business. By comparing two groups of students in different countries, it was also our aim to analyze the influence of cultural context on their entrepreneurial attitude. Participants The subjects of our study were a group of students from the University of Santiago de Chile (Chile) and another group of students from the University of Granada (Spain). A total of 499 valid questionnaires were collected (45.3% from Chile and 54.7% from Spain). Regarding the gender of the respondents, there were more women (n=314) than men (n=185) who participated in the study. This inequality was characteristic of both countries. The age of the respondents ranged from 19 to 45 years, and their mean age was 23.55 years (σx=3.10). Materials Three different questionnaires were used in this study: Entrepreneurial motivation questionnaire: This questionnaire was designed by the authors and consisted of six questions (see Annex 1). It focused on two variables: - Attitudes towards starting a business. This variable was measured with two questions regarding intention to create a company both individually and collectively. - Perceived social support for starting a business. This part was composed of four scalar questions in which the respondent was asked to evaluate his/her perception of the support received from other people and institutions. Value Questionnaire: For our study, we used the Spanish version (Ros and Grad 1991) of the Schwartz Value Survey (SVS) (Schwartz, 1992). Sociodemographic questionnaire: The third questionnaire was used to elicit socio-demographic data from the respondents, such as their degree program, age, gender, and the profession of their parents. Results The analysis of the data reflected individual differences in the intention to start a business. In addition, when a correlational analysis of both the Spanish and Chilean sample was performed, there was a significant and positive correlation between the intention to independently start a business and the male gender of the participant. This was true for both the Spanish students (r xy =0.10 p < 0.01) and the Chilean students (r xy =0.18 p < 0.01). No such statistical significance was observed in correlations related to the intention to initiate a business venture with partners. Furthermore, age positively correlated with the intention to create both types of business in the Chilean sample (r xy =0.30 p=0.00 for independently started businesses and r xy =0.23 p=0.00 for businesses started with associates). However, this did not occur in the Spanish sample. Regarding the first hypothesis of our study, our initial premise was that the existence of a family tradition of entrepreneurship would be positively related with the intention of creating a firm. The data obtained showed a positive correlation with the intention of starting a business on one s own. However when a linear regression was performed, there was no causal relation (for starting businesses either independently or collectively). In any case, when the results of the two countries were compared, they showed that in the Spanish sample, there was a causal relation with the intention to start a business independently (β=0.17 p=0.03). The same cannot be said for the Chilean group (β=-0.12 p=0.89). When the data were analyzed, in terms of degree programs in which students were enrolled, only the students in business-related degrees showed a significant and positive correlation with having a parent entrepreneur (rs= 0.27 p=0.01). This was not true for students in other degree programs. For this reason, Hypothesis 1 was only verified in the Spanish sample. In regards to Hypothesis 2, which stated that subjects with an individualistic pattern of values would have a higher intention to start a business, the data collected confirmed this relation. Accordingly, students with individualistic values showed a significant and positive correlation with the intention to create a business independently as well as collectively (r xy =0.25 p=0.00, and r xy =0.24 p=0.00, respectively). Nevertheless, this did not occur with those students with predominantly collectivistic values (r xy =-0.02 p=0.56 and r xy =-0.04 p=0.23), where the correlation was negative and not significant. A regression analysis showed that there was a causal relation between individualistic values and starting a business independently (β=0.15 p=0.01), as well as starting it with other business partners. This verified Hypothesis 2. When the analysis was based on the degree programs of the students, there was a positive correlation between individualistic values and the intention to start a business although this was only significant in students studying engineering degrees (r xy = 0.26 p < 0.05) and business-related degrees (r xy = 0.23 p < 0.05). This was not the case for students in other degree programs (r xy = 0.19 p=0.11). Another variable that had a positive correlation with the intention to start a business was country of origin. The descriptive analyses showed how the Chilean group had a higher mean score than the Spanish group regarding the probability of starting a business. This was true for independent business start-up (mean=64.82 vs. mean=42.86) as well as for collective business start-up with associates (mean=70.48 vs. mean=49.63). The regression analysis showed that there was a relation between country of origin and the intention to start a business, independently (β=-0.32 p=0.00) as well as collectively (β=-0.12 p=0.03). This verified Hypothesis 3. Finally, Hypothesis 4 underlined the importance of social support in the business start-up process. Table 3 shows that the intention to start a business (either individually or with others) only correlated with the perceived support from the university, but not from other potential agents (i.e. parents, friends, and government). A regression analysis again showed that only university support affected the probability of starting a business independently (β=0.23 p=0.00) or collectively with other business partners (β=0.17 p=0.03). The same did not occur with parental support (β=-0.58 p=0.26; β=-0.23 p=0.67); support from friends (β=-0.76 p=0.16; β=-0.01 p=0.95); or government support (β=-0.10 p=0.07; β=- 0.67 p=0.22). None of these had a causal relationship with either the individual or collective intention to create a firm. Consequently, the university provided the students with the greatest incentive for entrepreneurial activity. Discussion and conclusions In regard to models of family socialization, it was not possible to verify if those models were previous to the intention to start a business except in one subgroup of the Spanish sample. Consequently, since the respondents did not perceive support from family, friends or government, this lack was compensated for by the perceived support from the university. Thus, for the students, the university was played a key role in the advancement and support of entrepreneurial activity. Our results point to the fact that the university seems to compensate for the initial perceived lack of social support. However, it also is an authentic school for entrepreneurs since it creates and foments an environment, culture, and values oriented towards entrepreneurship. This is a crucial factor since the university thus becomes a fundamental tool for the development of entrepreneurial spirit and practice. Another surprising fact is that men seem to have a greater predisposition to start businesses than women (even though there is a positive relation for female students as well). The same does not occur when it comes to starting businesses with partners or associates. In all likelihood, stereotypes, such as risk or power, are socially speaking, more associated with the masculine gender. For this reason, men show a higher intention towards the independent creation of businesses (a characteristic frequently associated with the conventional concept of entrepreneur).The particularity observed in our study was that the predominance of personal and individualistic values affected the intention to start any type of business (either independently or collectively). This is in contrast with the idea that people with predominantly collectivistic values prefer to start a business with other business partners than those with a stronger pattern of individualistic values. Regarding country of origin, Chilean students showed a greater interest in and intention of starting a business (both independently and collectively) than Spanish students. The degree program was another variable with differentiated behavior. Thus, students in technological and business degree programs, who had prominently individualistic values, had a higher intention of starting a business. This highlights the fact that choice of degree is crucial, and that people who decide to enroll in these types of degree programs are more inclined to orient their career towards the business world and the creation of firms. In conclusion, the results of our study showed differences between the samples from Spain and Chile. The characterization of these proto-entrepreneurs is important. In other words, assuming that these students a more inclined per se to start a firm or company, what is then necessary is to create differentiated strategies directed at other groups who are not as predisposed towards entrepreneurship. © 2018 CIRIEC-España.; La Universidad juega un papel fundamental en la formación no solo de capacidades técnicas, sino también en el desarrollo de actitudes. En este sentido, una de sus responsabilidades es el fomento y apoyo del espíritu emprendedor entre sus estudiantes, en muchos casos en forma de empresas de participación. Sin embargo, estas actitudes emprendedoras se verán afectadas por elementos culturales y nacionales. El presente artículo desarrolla un estudio con el objetivo de conocer los antecedentes de la actitud emprendedora en estudiantes universitarios de dos países, lo cual puede ser de gran utilidad en los procesos de selección en programas universitarios de formación y fomento de empresas. Para estudiar tal objetivo se llevó a cabo un estudio transcultural con 499 estudiantes universitarios chilenos (n=226) y españoles (n=273) de tres ramas del conocimiento (empresas, tecnológicas y otras). De los resultados obtenidos se observó que la muestra española estaba más influenciada por factores sociales y familiares que en la muestra chilena, en la cual prevalecían otros factores de carácter más individual. En cualquier caso, se observó también la importancia del apoyo de la Universidad en el proceso de creación de empresas. El estudio muestra, finalmente, perfiles actitudinales específicos distintos de emprendimiento atendiendo a diferencias culturales. © 2018 CIRIEC-España.